Food wastage management at the South African Military Academy officer’s mess - Moss, Nomboniso; Henrico, Ivan; Smit, Hennie (Scientia Militaria - South African Journal of Military Studies, 2021)
Globally, an estimated one-third of the total of food produced for human consumptionis never consumed. This affects food security. South Africa has obligations to meetinternational commitments to reduce food wastage. The United Nations SustainableDevelopment Goal (SDG) 12.3 aims to reduce food loss through wastage by 30 per centby 2030. To contribute to the achievement of this goal, South Africa has to formulatepolicies to reduce food loss to achieve national food security. The South AfricanNational Defence Force (SANDF), as an organ of the state, should align with nationalpolicies aimed at reducing food loss and waste. The current study was conducted at theSouth African Military Academy (SAMA), an institution of higher learning for SANDFmembers. The institution has a catering facility that serves approximately 350 residentstudents and other living-in members375 daily. To date, no research has been done onfood wastage management either in the broader SANDF or at this institution. Thislack of information and analysis on food wastage management in the military in SouthAfrica prompted the current research. The study analysed food wastage management atthe SAMA mess to identify the level of knowledge and skills of SAMA officers’ messpersonnel regarding the status of food wastage and best management practices. Throughthis qualitative study, online semi-structured interviews, using Microsoft Teams, wereutilised to collect data from SAMA mess personnel. The findings revealed that there areset measures in place at the SAMA mess for managing food wastage, such as bookingmeals in advance and being able to repurpose food. The participants also indicated thatmost SAMA chefs are trained in food wastage management and possess the necessaryskills to reduce food wastage in the mess; yet, not optimally so. Recommendations fromthis research are that more and improved training of personnel, as well as awarenessprogrammes among mess staff and SAMA students would further reduce food wastage.Implementing such food wastage management measures would benefit the SAMAand the SANDF, and would contribute to national food wastage management and therealisation of the United Nations SDG 12.3.